Halophytes.tn: an innovative database for Tunisian halophyte plant identification, distribution and characterization. (19th March 2022) - Merchaoui, Henda; Ksouri, Riadh; Abdelly, Chedly; Hanana, Mohsen
Abstract: Halophytes.tn (http://halophytes.rnrt.tn/ ) is a web-based database of Tunisian halophyte species. Halophytes are salt-tolerant plants able to grow above 85 mM of salt, even up to 2 M as for Tecticornia spp. Tunisia, a North African country located on the Mediterranean border, covering ∼165 000 km 2, harbors several types of saline habitats and biotopes where halophytes preferably vegetate. With ∼6000 worldwide and over 420 Tunisian species, halophytes represent a huge potential in several fields, including desalination, phytoremediation, agrofarming, medicinal use, industrial applications, pharmacology and even nanotechnology. We describe the practical and technical steps followed and bioinformatics tools used to conceive and design the first Tunisian halophytes database, enabling species identification and characterization. As a first version, information about botany, morphology, ecophysiology and biochemistry were provided for the identified species with their sites of growing in Tunisia, first step of biodiversity conservation, management and valorization. The database will be regularly maintained, updated and enriched to achieve the goal of whole Tunisian halophyte species and fit the needs of scientists and all category of users.Database URL:  http://halophytes.rnrt.tn/